Copyright (c) 1989 Association of Mizar Users
environ vocabulary ARYTM, ARYTM_1, ARYTM_3, RELAT_1, ABSVALUE; notation ORDINAL1, XCMPLX_0, XREAL_0, REAL_1; constructors REAL_1, XCMPLX_0, XREAL_0, XBOOLE_0; clusters XREAL_0, REAL_1, ARYTM_3, ZFMISC_1, XBOOLE_0; requirements REAL, NUMERALS, SUBSET, ARITHM; theorems XREAL_0, AXIOMS, REAL_1, XCMPLX_0, XCMPLX_1; begin reserve x, y, z, s, t for real number; definition let x; func abs x -> real number equals :Def1: x if 0 <= x otherwise -x; coherence; consistency; projectivity by REAL_1:66; end; definition let x be Real; redefine func abs x -> Real; coherence by XREAL_0:def 1; end; canceled 4; theorem Th5: 0 <= abs(x) proof x < 0 implies 0 <= abs(x) proof assume A1: x < 0; then abs(x) = -x by Def1; hence thesis by A1,REAL_1:26,50; end; hence thesis by Def1; end; theorem Th6: x <> 0 implies 0 < abs(x) proof assume x <> 0; then A1: x < 0 or 0 < x by AXIOMS:21; x < 0 implies 0 < abs(x) proof assume A2: x < 0; then abs(x) = -x by Def1; hence thesis by A2,REAL_1:66; end; hence thesis by A1,Def1; end; theorem x = 0 iff abs(x) = 0 by Def1,Th6; canceled; theorem abs(x) = -x & x <> 0 implies x < 0 proof assume that A1: abs(x) = -x and A2: x <> 0 and A3: not x < 0; 0 < x by A2,A3,REAL_1:def 5; then -x < 0 by REAL_1:26,50; hence contradiction by A1,A3,Def1; end; theorem Th10: abs(x*y) = abs(x) * abs(y) proof A1: x < 0 & y < 0 implies abs(x*y) = abs(x) * abs(y) proof assume that A2: x < 0 and A3: y < 0; A4: x * 0 < x * y by A2,A3,REAL_1:71; A5: abs(y) = -y by A3,Def1; A6: abs(x*y) = x * y by A4,Def1; A7: (-x) * (-y) = - ((-x) * y) by XCMPLX_1:175; -((-x) * y) = -(-(x * y)) by XCMPLX_1:175; hence thesis by A2,A5,A6,A7,Def1; end; A8: x < 0 & 0 < y implies abs(x*y) = abs(x) * abs(y) proof assume that A9: x < 0 and A10: 0 < y; A11:x * y < 0 * y by A9,A10,REAL_1:70; abs(x) = -x by A9,Def1; then abs(x) * abs(y) = (-x) * y by A10,Def1; then abs(x) * abs(y) = -(x * y) by XCMPLX_1:175; hence thesis by A11,Def1; end; A12:x < 0 & y = 0 implies abs(x*y) = abs(x) * abs(y) proof assume that x < 0 and A13: y = 0; abs(y) = 0 by A13,Def1; hence thesis by A13; end; A14: 0 <= x & 0 <= y implies abs(x*y) = abs(x) * abs(y) proof assume that A15: 0 <= x and A16: 0 <= y; A17: 0 * y <= x * y by A15,A16,AXIOMS:25; abs(x) = x by A15,Def1; then abs(x) * abs(y) = x * y by A16,Def1; hence thesis by A17,Def1; end; A18: 0 < x & y < 0 implies abs(x*y) = abs(x) * abs(y) proof assume that A19: 0 < x and A20: y < 0; A21: x * y < x * 0 by A19,A20,REAL_1:70; abs(x) = x by A19,Def1; then abs(x) * abs(y) = x * (-y) by A20,Def1; then abs(x) * abs(y) = -(x * y) by XCMPLX_1:175; hence thesis by A21,Def1; end; x = 0 implies abs(x*y) = abs(x) * abs(y) proof assume A22: x = 0; then abs(x) = 0 by Def1; hence thesis by A22; end; hence thesis by A1,A8,A12,A14,A18,REAL_1:def 5; end; theorem Th11: -abs(x) <= x & x <= abs(x) proof A1: x < 0 implies -abs(x) <= x & x <= abs(x) proof assume A2: x < 0; then A3: abs(x) = -x by Def1; 0 < -x by A2,REAL_1:66; hence thesis by A2,A3,AXIOMS:22; end; 0 <= x implies -abs(x) <= x & x <= abs(x) proof assume A4: 0 <= x; then A5: abs(x) = x by Def1; -x <= 0 by A4,REAL_1:26,50; hence thesis by A4,A5,AXIOMS:22; end; hence thesis by A1; end; theorem Th12: -y <= x & x <= y iff abs(x) <= y proof A1: -y <= x & x <= y implies abs(x) <= y proof assume that A2: -y <= x and A3: x <= y; -x <= -(-y) by A2,REAL_1:50; then x < 0 implies abs(x) <= y by Def1; hence thesis by A3,Def1; end; abs(x) <= y implies -y <= x & x <= y proof assume A4: abs(x) <= y; 0 <= abs(x) by Th5; then A5: 0 <= y by A4,AXIOMS:22; A6: 0 < x or x < 0 or x = 0 by AXIOMS:21; A7: 0 < x implies -y <= x & x <= y proof assume A8: 0 < x; -y <= 0 by A5,REAL_1:26,50; hence thesis by A4,A8,Def1,AXIOMS:22; end; x < 0 implies -y <= x & x <= y proof assume A9: x < 0; then -x <= y by A4,Def1; then -y <= -(-x) by REAL_1:50; hence thesis by A5,A9,AXIOMS:22; end; hence thesis by A5,A6,A7,REAL_1:26,50; end; hence thesis by A1; end; theorem Th13: abs(x+y) <= abs(x) + abs(y) proof A1: -abs(x) <= x & x <= abs(x) by Th11; -abs(y) <= y & y <= abs(y) by Th11; then -abs(x) + -abs(y) <= x + y & x + y <= abs(x) + abs(y) by A1,REAL_1:55; then (-abs(x)) - abs(y) <= x + y & x + y <= abs(x) + abs(y) by XCMPLX_0:def 8 ; then -(abs(y) -(-abs(x))) <= x + y & x + y <= abs(x) + abs(y) by XCMPLX_1:143; then -(abs(y) + -(-abs(x))) <= x + y & x + y <= abs(x) + abs(y) by XCMPLX_0:def 8; hence thesis by Th12; end; theorem Th14: x <> 0 implies abs(x) * abs(1/x) = 1 proof assume A1: x <> 0; A2: abs(x) * abs(1/x) = abs(x * (1/x)) by Th10; abs(x * (1/x)) = abs 1 by A1,XCMPLX_1:107; hence thesis by A2,Def1; end; theorem Th15: abs(1/x) = 1/abs(x) proof per cases; suppose A1: x = 0; hence abs(1/x) = abs(1*0") by XCMPLX_0:def 9 .= abs (1*0) by XCMPLX_0:def 7 .= 0 by Def1 .= 1*0" by XCMPLX_0:def 7 .= 1/0 by XCMPLX_0:def 9 .= 1/abs(x) by A1,Def1; suppose A2: x <> 0; then (abs(x) * abs(1/x)) * (1/abs(x)) = 1 * (1/abs(x)) by Th14; then A3: abs(1/x) * (abs(x) * (1/abs(x))) = 1/abs(x) by XCMPLX_1:4; abs(x) <> 0 by A2,Th6; then abs(1/x) * 1 = 1/abs(x) by A3,XCMPLX_1:107; hence thesis; end; theorem abs(x/y) = abs(x)/abs(y) proof x/y = x*(1*y") by XCMPLX_0:def 9 .= x*(1/y) by XCMPLX_0:def 9; then abs(x/y) = abs(x) * abs(1/y) by Th10; then abs(x/y) = (abs(x)/1) * (1/abs(y)) by Th15; then abs(x/y) = (abs(x) * 1 )/(1 * abs(y)) by XCMPLX_1:77; hence thesis; end; theorem Th17: abs(x) = abs(-x) proof A1: x < 0 or 0 < x or x = 0 by AXIOMS:21; A2: x < 0 implies abs(x) = abs(-x) proof assume x < 0; then abs(x) = -x by Def1; hence thesis; end; 0 < x implies abs(x) = abs(-x) proof assume 0 < x; then -x < 0 by REAL_1:26,50; then abs(-x) = -(-x) by Def1; hence thesis; end; hence thesis by A1,A2; end; theorem Th18: abs(x) - abs(y) <= abs(x-y) proof x = x + 0; then x = x + ( -y + y ) by XCMPLX_0:def 6 .= ( x + -y ) + y by XCMPLX_1:1 .= ( x - y ) + y by XCMPLX_0:def 8; then abs(x) <= abs(x-y) + abs(y) by Th13; hence thesis by REAL_1:86; end; theorem abs(x-y) <= abs(x) + abs(y) proof abs(x-y) = abs(x + -y) by XCMPLX_0:def 8; then abs(x-y) <= abs(x) + abs(-y) by Th13; hence thesis by Th17; end; canceled; theorem abs(x) <= z & abs(y) <= t implies abs(x+y) <= z + t proof assume that A1: abs(x) <= z and A2: abs(y) <= t; A3: abs(x+y) <= abs(x) + abs(y) by Th13; abs(x) + abs(y) <= z + t by A1,A2,REAL_1:55; hence thesis by A3,AXIOMS:22; end; theorem abs(abs(x) - abs(y)) <= abs(x-y) proof A1: abs(x) - abs(y) <= abs(x-y) by Th18; A2: abs(y) - abs(x) <= abs(y - x) by Th18; A3: abs(y - x) = abs(-(1 * (x - y))) by XCMPLX_1:143 .= abs((-1) * (x - y)) by XCMPLX_1:175 .= abs(-1) * abs(x-y) by Th10; A4: abs(-1) = -(-1) by Def1 .= 1; -( abs(x) - abs(y) ) <= abs(y - x) by A2,XCMPLX_1:143; then -abs(x-y) <= -( -( abs(x) - abs(y) ) ) by A3,A4,REAL_1:50; hence thesis by A1,Th12; end; canceled; theorem 0 <= x * y implies abs(x+y) = abs(x) + abs(y) proof assume A1: 0 <= x * y; A2: x * y = 0 implies abs(x+y) = abs(x) + abs(y) proof assume A3: x * y = 0; A4: x = 0 implies abs(x+y) = abs(x) + abs(y) proof assume A5: x = 0; then abs(x) + abs(y) = 0 + abs(y) by Def1 .= abs(y); hence thesis by A5; end; y = 0 implies abs(x+y) = abs(x) + abs(y) proof assume A6: y = 0; then abs(x) + abs(y) = abs(x) + 0 by Def1 .= abs(x); hence thesis by A6; end; hence thesis by A3,A4,XCMPLX_1:6; end; 0 < x * y implies abs(x+y) = abs(x) + abs(y) proof assume A7: 0 < x * y; A8: 0 < x * y implies x < 0 & y < 0 or 0 < x & 0 < y proof assume A9: 0 < x * y; then A10: x <> 0 & y <> 0; A11: x < 0 & 0 < y implies x * y < x * 0 by REAL_1:71; 0 < x & y < 0 implies x * y < x * 0 by REAL_1:70; hence thesis by A9,A10,A11,AXIOMS:21; end; A12: 0 < x & 0 < y implies abs(x+y) = abs(x) + abs(y) proof assume that A13: 0 < x and A14: 0 < y; A15: 0 + 0 < x + y by A13,A14,REAL_1:67; abs(x) = x by A13,Def1; then abs(x) + abs(y) = x + y by A14,Def1; hence thesis by A15,Def1; end; x < 0 & y < 0 implies abs(x+y) = abs(x) + abs(y) proof assume that A16: x < 0 and A17: y < 0; A18: x + y < 0 + 0 by A16,A17,REAL_1:67; abs(x) = -x by A16,Def1; then abs(x) + abs(y) = -(1 * x) + -(1 * y) by A17,Def1 .= (-1) * x + -(1 * y) by XCMPLX_1:175 .= (-1) * x + (-1) * y by XCMPLX_1:175 .= (-1) * ( x + y ) by XCMPLX_1:8 .= - ( 1 * ( x + y ) ) by XCMPLX_1:175 .= - ( x + y ); hence thesis by A18,Def1; end; hence thesis by A7,A8,A12; end; hence thesis by A1,A2,REAL_1:def 5; end; theorem abs(x+y) = abs(x) + abs(y) implies 0 <= x * y proof assume that A1: abs(x+y) = abs(x) + abs(y) and A2: not ( 0 <= x * y ); A3: x * y < 0 implies x < 0 & 0 < y or 0 < x & y < 0 proof assume A4: x * y < 0; then A5: x <> 0 & y <> 0; A6: x < 0 & y < 0 implies 0 * x < x * y by REAL_1:71; 0 < x & 0 < y implies x * 0 < x * y by REAL_1:70; hence thesis by A4,A5,A6,AXIOMS:21; end; A7: x < 0 & 0 < y & x + y < 0 implies not ( abs(x+y) = abs(x) + abs(y) ) proof assume that A8: x < 0 and A9: 0 < y and A10: x + y < 0; -y < 0 by A9,REAL_1:26,50; then -y + 0 < 0 + y by A9,REAL_1:67; then -(1 * x) + -y < -x + y by REAL_1:53; then (-1) * x + -(1 * y) < -x + y by XCMPLX_1:175; then (-1) * x + (-1) * y < -x + y by XCMPLX_1:175; then (-1) * ( x + y ) < -x + y by XCMPLX_1:8; then A11: -( 1 * ( x + y ) ) < -x + y by XCMPLX_1:175; A12: abs(x) = -x by A8,Def1; abs(y) = y by A9,Def1; hence thesis by A10,A11,A12,Def1; end; A13: x < 0 & 0 < y & 0 <= x + y implies not ( abs(x+y) = abs(x) + abs(y) ) proof assume that A14: x < 0 and A15: 0 < y and A16: 0 <= x + y; 0 < -x by A14,REAL_1:66; then x + 0 < 0 + -x by A14,REAL_1:67; then A17: x + y < -x + y by REAL_1:53; A18: abs(x) = -x by A14,Def1; abs(y) = y by A15,Def1; hence thesis by A16,A17,A18,Def1; end; A19: 0 < x & y < 0 & x + y < 0 implies not ( abs(x+y) = abs(x) + abs(y) ) proof assume that A20: 0 < x and A21: y < 0 and A22: x + y < 0; -x < 0 by A20,REAL_1:26,50; then -x + 0 < 0 + x by A20,REAL_1:67; then -(1 * x) + -y < x + -y by REAL_1:53; then (-1) * x + -(1 * y) < x + -y by XCMPLX_1:175; then (-1) * x + (-1) * y < x + -y by XCMPLX_1:175; then (-1) * ( x + y ) < x + -y by XCMPLX_1:8; then A23: - (1 * ( x + y )) < x + -y by XCMPLX_1:175; A24: abs(x) = x by A20,Def1; abs(y) = -y by A21,Def1; hence thesis by A22,A23,A24,Def1; end; 0 < x & y < 0 & 0 <= x + y implies not ( abs(x+y) = abs(x) + abs(y) ) proof assume that A25: 0 < x and A26: y < 0 and A27: 0 <= x + y; 0 < -y by A26,REAL_1:66; then 0 + y < -y + 0 by A26,REAL_1:67; then A28: x + y < x + -y by REAL_1:53; A29: abs(x) = x by A25,Def1; abs(y) = -y by A26,Def1; hence thesis by A27,A28,A29,Def1; end; hence contradiction by A1,A2,A3,A7,A13,A19; end; theorem abs(x+y)/(1 + abs(x+y)) <= abs(x)/(1 + abs(x)) + abs(y)/(1 +abs(y)) proof set a = abs(x), b = abs(y), c = abs(x+y); A1: c <= a + b by Th13; A2: 0 <= a by Th5; A3: 0 <= b by Th5; A4: 0 <= c by Th5; A5: 0 + 0 <= a + b by A2,A3,REAL_1:55; then A6: 0 + 0 < 1 + (a + b) by REAL_1:67; A7: 0 < 1 + (a + b) by A5,REAL_1:67; A8: 0 < 1 + a + b by A6,XCMPLX_1:1; A9: 0 + 0 < 1 + c by A4,REAL_1:67; A10: 0 + 0 < 1 + a by A2,REAL_1:67; A11: 0 + 0 < 1 + b by A3,REAL_1:67; s <= t & 0 < 1 + s & 0 < 1 + t implies s/(1 + s) <= t/(1 + t) proof assume that A12: s <= t and A13: 0 < 1 + s and A14: 0 < 1 + t; s * 1 + s * t <= t + s * t by A12,AXIOMS:24; then s * (1 + t) <= 1 * t + s * t by XCMPLX_1:8; then A15: s * (1 + t) <= (1 + s) * t by XCMPLX_1:8; A16: 0 < (1 + s)" by A13,REAL_1:72; A17: 0 < (1 + t)" by A14,REAL_1:72; s * (1 + t) * (1 + s)" <= t * (1 + s) * (1 + s)" by A15,A16, AXIOMS:25; then s * (1 + t) * (1 + s)" <= t * ((1 + s) * (1 + s)") by XCMPLX_1:4; then s * (1 + t) * (1 + s)" <= t * 1 by A13,XCMPLX_0:def 7; then (s * (1 + s)") * (1 + t) <= t by XCMPLX_1:4; then (s * (1 + s)") * (1 + t) * (1 + t)" <= t * (1 + t)" by A17,AXIOMS:25; then (s * (1 + s)") * ((1 + t) * (1 + t)") <= t * (1 + t)" by XCMPLX_1:4; then (s * (1 + s)") * 1 <= t * (1 + t)" by A14,XCMPLX_0:def 7; then s/(1 + s) <= t * (1 + t)" by XCMPLX_0:def 9; hence thesis by XCMPLX_0:def 9; end; then c/(1 + c) <= (a + b)/(1 + (a + b)) by A1,A7,A9; then A18: c/(1 + c) <= (a + b)/(1 + a + b) by XCMPLX_1:1; (a + b)/(1 + a + b) <= a/(1 + a) + b/(1 + b) proof A19: (a + b)/(1 + a + b) = a/(1 + a + b) + b/(1 + a + b) by XCMPLX_1:63; A20: 0 < 1 + a & 0 < 1 + a + b implies a/(1 + a + b) <= a/(1 + a) proof assume that A21: 0 < 1 + a and A22: 0 < 1 + a + b; 0 * b <= a * b by A2,A3,AXIOMS:25; then 0 + a <= a * b + a by AXIOMS:24; then a <= a * b + a * 1; then a <= a * (1 + b) by XCMPLX_1:8; then a * 1 + a * a <= a * (1 + b) + a * a by AXIOMS:24; then a * (1 + a) <= a * (1 + b) + a * a by XCMPLX_1:8; then a * (1 + a) <= a * ((1 + b) + a) by XCMPLX_1:8; then A23: a * (1 + a) <= a * (1 + a + b) by XCMPLX_1:1; A24: 0 <= (1 + a)" by A21,REAL_1:72; A25: 0 <= (1 + a + b)" by A22,REAL_1:72; a * (1 + a) * (1 + a)" <= a * (1 + a + b) * (1 + a)" by A23,A24,AXIOMS:25; then a * ((1 + a) * (1 + a)") <= a * (1 + a + b) * (1 + a)" by XCMPLX_1:4; then a * 1 <= a * (1 + a + b) * (1 + a)" by A10,XCMPLX_0:def 7; then a <= (a * (1 + a)") * (1 + a + b) by XCMPLX_1:4; then a * (1 + a + b)" <= (a * (1 + a)") * (1 + a + b) * (1 + a + b)" by A25,AXIOMS:25; then a * (1 + a + b)" <= (a * (1 + a)") * ((1 + a + b) * ( 1 + a + b)") by XCMPLX_1:4; then a * (1 + a + b)" <= (a * (1 + a)") * 1 by A8,XCMPLX_0:def 7 ; then a/(1 + a + b) <= a * (1 + a)" by XCMPLX_0:def 9; hence thesis by XCMPLX_0:def 9; end; 0 < 1 + b & 0 < 1 + a + b implies b/(1 + a + b) <= b/(1 + b) proof assume that A26: 0 < 1 + b and A27: 0 < 1 + a + b; 0 * b <= a * b by A2,A3,AXIOMS:25; then 0 + b <= a * b + b by AXIOMS:24; then b <= a * b + 1 * b; then b <= (1 + a) * b by XCMPLX_1:8; then b * 1 + b * b <= (1 + a) * b + b * b by AXIOMS:24; then b * (1 + b) <= (1 + a) * b + b * b by XCMPLX_1:8; then A28: b * (1 + b) <= b * (1 + a + b) by XCMPLX_1:8; A29: 0 <= (1 + b)" by A26,REAL_1:72; A30: 0 <= (1 + a + b)" by A27,REAL_1:72; (b * (1 + b)) * (1 + b)" <= (b * (1 + a + b)) * (1 + b)" by A28,A29,AXIOMS:25; then b * ((1 + b) * (1 + b)") <= (b * (1 + a + b)) * (1 + b)" by XCMPLX_1:4; then b * 1 <= (b * (1 + a + b)) * (1 + b)" by A11,XCMPLX_0:def 7 ; then b <= (b * (1 + b)") * (1 + a + b) by XCMPLX_1:4; then b * (1 + a + b)" <= ((b * (1 + b)") * (1 + a + b )) * (1 + a + b)" by A30,AXIOMS:25; then b * (1 + a + b)" <= (b * (1 + b)") * ((1 + a + b) * (1 + a + b)") by XCMPLX_1:4; then b * (1 + a + b)" <= (b * (1 + b)") * 1 by A8,XCMPLX_0:def 7 ; then b/(1 + a + b) <= b * (1 + b)" by XCMPLX_0:def 9; hence thesis by XCMPLX_0:def 9; end; hence thesis by A3,A10,A19,A20,REAL_1:55,67; end; hence thesis by A18,AXIOMS:22; end; definition let x; func sgn x equals :Def2: 1 if 0 < x, -1 if x < 0 otherwise 0; coherence; consistency; end; definition let x; cluster sgn x -> real; coherence proof 0 < x or 0 > x or x = 0 by REAL_1:def 5; hence thesis by Def2; end; end; definition let x be Real; redefine func sgn x -> Real; coherence by XREAL_0:def 1; end; canceled 4; theorem sgn x = 1 implies 0 < x proof assume that A1: sgn x = 1 and A2: not ( 0 < x ); x < 0 or x = 0 by A2,REAL_1:def 5; hence contradiction by A1,Def2; end; theorem sgn x = -1 implies x < 0 proof assume that A1: sgn x = -1 and A2: not ( x < 0 ); 0 < x or x = 0 by A2,REAL_1:def 5; hence contradiction by A1,Def2; end; theorem Th33: sgn x = 0 implies x = 0 proof assume that A1: sgn x = 0 and A2: x <> 0; 0 < x or x < 0 by A2,AXIOMS:21; hence contradiction by A1,Def2; end; theorem x = abs(x) * sgn x proof A1: 0 < x implies x = abs(x) * sgn x proof assume A2: 0 < x; then abs(x) = x by Def1; then abs(x) * sgn x = x * 1 by A2,Def2; hence thesis; end; A3: x < 0 implies x = abs(x) * sgn x proof assume A4: x < 0; then abs(x) = -x by Def1; then abs(x) * sgn x = (-x) * (-1) by A4,Def2 .= -(-( x * 1 )) by XCMPLX_1:176 .= x; hence thesis; end; x = 0 implies x = abs(x) * sgn x proof assume A5: x = 0; then sgn x = 0 by Def2; hence thesis by A5; end; hence thesis by A1,A3,AXIOMS:21; end; theorem Th35: sgn (x * y) = sgn x * sgn y proof A1: 0 < x & 0 < y implies sgn (x * y) = sgn x * sgn y proof assume that A2: 0 < x and A3: 0 < y; A4: 0 * y < x * y by A2,A3,REAL_1:70; A5: sgn x = 1 by A2,Def2; sgn y = 1 by A3,Def2; hence thesis by A4,A5,Def2; end; A6: 0 < x & y < 0 implies sgn (x * y) = sgn x * sgn y proof assume that A7: 0 < x and A8: y < 0; A9: x * y < 0 * y by A7,A8,REAL_1:71; sgn y = -1 by A8,Def2; then sgn x * sgn y = 1 * (-1) by A7,Def2 .= -1; hence thesis by A9,Def2; end; A10: x < 0 & 0 < y implies sgn (x * y) = sgn x * sgn y proof assume that A11: x < 0 and A12: 0 < y; A13: x * y < 0 * y by A11,A12,REAL_1:70; sgn y = 1 by A12,Def2; then sgn x * sgn y = -1 by A11,Def2; hence thesis by A13,Def2; end; A14: x < 0 & y < 0 implies sgn (x * y) = sgn x * sgn y proof assume that A15: x < 0 and A16: y < 0; A17: x * 0 < x * y by A15,A16,REAL_1:71; sgn y = -1 by A16,Def2; then sgn x * sgn y = (-1) * (-1) by A15,Def2 .= 1; hence thesis by A17,Def2; end; x = 0 or y = 0 implies sgn (x * y) = sgn x * sgn y proof assume A18: x = 0 or y = 0; then sgn x = 0 or sgn y = 0 by Def2; hence thesis by A18,Def2; end; hence thesis by A1,A6,A10,A14,AXIOMS:21; end; theorem sgn sgn x = sgn x proof A1: 0 < x or x < 0 or x = 0 by AXIOMS:21; A2: 0 < x implies sgn sgn x = sgn x proof assume A3: 0 < x; then sgn sgn x = sgn 1 by Def2 .= 1 by Def2; hence thesis by A3,Def2; end; x < 0 implies sgn sgn x = sgn x proof assume A4: x < 0; then sgn sgn x = sgn (-1) by Def2 .= -1 by Def2; hence thesis by A4,Def2; end; hence thesis by A1,A2,Def2; end; theorem sgn (x + y) <= sgn x + sgn y + 1 proof A1: 0 < x & 0 < y implies sgn (x + y) <= sgn x + sgn y + 1 proof assume that A2: 0 < x and A3: 0 < y; A4: 0 + 0 < x + y by A2,A3,REAL_1:67; A5: sgn x = 1 by A2,Def2; A6: sgn y = 1 by A3,Def2; sgn x < sgn x + 1 by REAL_1:69; then sgn x + 0 < sgn x + 1 + 1 by REAL_1:67; hence thesis by A4,A5,A6,Def2; end; A7: 0 < x & y < 0 implies sgn (x + y) <= sgn x + sgn y +1 proof assume that A8: 0 < x and A9: y < 0; sgn x = 1 by A8,Def2; then A10: sgn x + sgn y + 1 = 1 + -1 + 1 by A9,Def2 .= 1; A11:x + y < 0 or x + y = 0 or 0 < x + y by AXIOMS:21; A12: sgn (x + y) = 0 implies sgn (x + y) <= sgn x + sgn y + 1 by A10; sgn (x + y) = -1 implies sgn (x + y) <= sgn x + sgn y + 1 by A10; hence thesis by A10,A11,A12,Def2; end; A13: x < 0 & 0 < y implies sgn (x + y) <= sgn x + sgn y + 1 proof assume that A14: x < 0 and A15: 0 < y; sgn x = -1 by A14,Def2; then A16: sgn x + sgn y + 1 = -1 + 1 + 1 by A15,Def2 .= 1; A17:x + y < 0 or x + y = 0 or 0 < x + y by AXIOMS:21; A18: sgn (x + y) = 0 implies sgn (x + y) <= sgn x + sgn y + 1 by A16; sgn (x + y) = -1 implies sgn (x + y) <= sgn x + sgn y + 1 by A16; hence thesis by A16,A17,A18,Def2; end; A19: x < 0 & y < 0 implies sgn (x + y) <= sgn x + sgn y + 1 proof assume that A20: x < 0 and A21: y < 0; A22:x + y < 0 + 0 by A20,A21,REAL_1:67; sgn y = -1 by A21,Def2; then sgn x + sgn y + 1 = -1 + -1 + 1 by A20,Def2 .= -1; hence thesis by A22,Def2; end; x = 0 or y = 0 implies sgn (x + y) <= sgn x + sgn y + 1 proof A23: x = 0 implies sgn (x + y) <= sgn x + sgn y + 1 proof assume A24: x = 0; then sgn x + sgn y + 1 = 0 + sgn y + 1 by Def2 .= sgn y + 1; hence thesis by A24,REAL_1:69; end; y = 0 implies sgn (x + y) <= sgn x + sgn y + 1 proof assume A25: y = 0; then sgn x + sgn y + 1 = sgn x + 0 + 1 by Def2 .= sgn x + 1; hence thesis by A25,REAL_1:69; end; hence thesis by A23; end; hence thesis by A1,A7,A13,A19,AXIOMS:21; end; theorem Th38: x <> 0 implies sgn x * sgn (1/x) = 1 proof assume x <> 0; then sgn ( x * (1/x) ) = sgn 1 by XCMPLX_1:107; then sgn ( x * (1/x) ) = 1 by Def2; hence thesis by Th35; end; theorem Th39: 1/(sgn x) = sgn (1/x) proof per cases; suppose A1: x = 0; hence 1/(sgn x) = 1/0 by Def2 .= 1*0" by XCMPLX_0:def 9 .= 0 by XCMPLX_0:def 7 .= sgn(1*0) by Def2 .= sgn(1*0") by XCMPLX_0:def 7 .= sgn (1/x) by A1,XCMPLX_0:def 9; suppose A2: x <> 0; then A3: sgn x <> 0 by Th33; (sgn x * sgn (1/x)) * (1/(sgn x)) = 1 * (1/(sgn x)) by A2,Th38; then sgn (1/x) * (sgn x * (1/(sgn x))) = 1/(sgn x) by XCMPLX_1:4; then sgn (1/x) * 1 = 1 /(sgn x) by A3,XCMPLX_1:107; hence thesis; end; theorem sgn x + sgn y - 1 <= sgn ( x + y ) proof A1: x < 0 & y < 0 implies sgn x + sgn y - 1 <= sgn (x + y) proof assume that A2: x < 0 and A3: y < 0; A4: x + y < 0 + 0 by A2,A3,REAL_1:67; A5: sgn x = -1 by A2,Def2; A6: sgn y = -1 by A3,Def2; A7: sgn x = sgn (x + y) by A4,A5,Def2; sgn (x + y) + -1 - 1 < sgn (x + y) + -1 - 1 + 1 by REAL_1:69; then sgn (x + y) + -1 - 1 < sgn (x + y) + -1 + -1 + 1 by XCMPLX_0:def 8; then A8:sgn (x + y) + -1 - 1 < sgn (x + y) + -1 + ( -1 + 1 ) by XCMPLX_1:1; sgn (x + y) + -1 < sgn (x + y) + -1 + 1 by REAL_1:69; then sgn (x + y) + -1 < sgn (x + y) + (-1 + 1) by XCMPLX_1:1; hence thesis by A6,A7,A8,AXIOMS:22; end; A9: x < 0 & 0 < y implies sgn x + sgn y - 1 <= sgn (x + y) proof assume that A10: x < 0 and A11: 0 < y; sgn x = -1 by A10,Def2; then A12: sgn x + sgn y = -1 + 1 by A11,Def2 .= 0; x + y < 0 or x + y = 0 or 0 < x + y by AXIOMS:21; then sgn (x + y) = -1 or sgn (x + y) = 0 or sgn (x + y) = 1 by Def2; hence thesis by A12; end; A13: 0 < x & y < 0 implies sgn x + sgn y - 1 <= sgn (x + y) proof assume that A14: 0 < x and A15: y < 0; sgn x = 1 by A14,Def2; then A16:sgn x + sgn y = 1 + -1 by A15,Def2 .= 0; x + y < 0 or x + y = 0 or 0 < x + y by AXIOMS:21; then sgn (x + y) = -1 or sgn (x + y) = 0 or sgn (x + y) = 1 by Def2; hence thesis by A16; end; A17: 0 < x & 0 < y implies sgn x + sgn y - 1 <= sgn (x + y) proof assume that A18: 0 < x and A19: 0 < y; A20: 0 + 0 < x + y by A18,A19,REAL_1:67; sgn y = 1 by A19,Def2; then sgn x + sgn y - 1 = 1 + 1 - 1 by A18,Def2 .= 1; hence thesis by A20,Def2; end; x = 0 or y = 0 implies sgn x + sgn y - 1 <= sgn (x + y) proof assume A21: x = 0 or y = 0; A22: x = 0 implies sgn x + sgn y - 1 <= sgn (x + y) proof assume A23: x = 0; then A24: sgn x + sgn y - 1 = 0 + sgn y - 1 by Def2 .= sgn y - 1; sgn y - 1 < sgn y - 1 + 1 by REAL_1:69; then sgn y - 1 < sgn y + -1 + 1 by XCMPLX_0:def 8; then sgn y - 1 < sgn y + (-1 + 1) by XCMPLX_1:1; hence thesis by A23,A24; end; y = 0 implies sgn x + sgn y - 1 <= sgn (x + y) proof assume A25: y = 0; then A26: sgn x + sgn y - 1 = sgn x + 0 - 1 by Def2 .= sgn x - 1; sgn x - 1 < sgn x - 1 + 1 by REAL_1:69; then sgn x - 1 < sgn x + -1 + 1 by XCMPLX_0:def 8; then sgn x - 1 < sgn x + (-1 + 1) by XCMPLX_1:1; hence thesis by A25,A26; end; hence thesis by A21,A22; end; hence thesis by A1,A9,A13,A17,AXIOMS:21; end; theorem sgn x = sgn (1/x) proof per cases; suppose A1: x = 0; 1/0 = 1*0" by XCMPLX_0:def 9 .= 1*0 by XCMPLX_0:def 7; hence thesis by A1; suppose A2: x <> 0; A3: x < 0 implies sgn x = sgn (1/x) proof assume A4: x < 0; then sgn x = -1 by Def2; then sgn (1/x) = 1/(-1) by Th39; hence thesis by A4,Def2; end; 0 < x implies sgn x = sgn (1/x) proof assume A5: 0 < x; sgn (1/x) = 1/(sgn x) by Th39; then sgn (1/x) = 1/1 by A5,Def2 .= 1; hence thesis by A5,Def2; end; hence thesis by A2,A3,AXIOMS:21; end; theorem sgn (x/y) = (sgn x)/(sgn y) proof per cases; suppose A1: y = 0; hence sgn (x/y) = sgn (x*0") by XCMPLX_0:def 9 .= sgn (x*0) by XCMPLX_0:def 7 .= (sgn x)*0 by Def2 .= (sgn x)*0" by XCMPLX_0:def 7 .= (sgn x)/0 by XCMPLX_0:def 9 .= (sgn x)/(sgn y) by A1,Def2; suppose A2: y <> 0; x/y = (x/y) * 1 .= (x/y) * (y * (1/y)) by A2,XCMPLX_1:107 .= ((x/y) * y) * (1/y) by XCMPLX_1:4 .= x * (1/y) by A2,XCMPLX_1:88; then sgn (x/y) = sgn x * sgn (1/y) by Th35 .= ((sgn x)/1) * (1/(sgn y)) by Th39 .= (sgn x * 1)/(1 * sgn y) by XCMPLX_1:77 .= (sgn x)/(1 * sgn y); hence thesis; end;